An epoxide rearrangement-radical rearrangement approach to 6-substituted 2-azabicyclo[2.2.1]-5-heptenes: Synthesis of an epibatidine analogue - Hodgson, D; Maxwell, C; Matthews, I (1998)
Base-induced isomerisation of epoxide 9 gives an azanortricyclanol 10 which is a precursor for a novel free-radical induced rearrangement to 6-substituted 2-azabicyclo[2.2.1]-5-heptenes 14a-c; 14c (R = 6-chloro-3-pyridinyl) is converted to the epibatidine analogue 2.